Atrial natriuretic peptide levels in the sleep apnoea/hypopnoea syndrome. Issue 9 (September 1994) - Mackay, T W; Fitzpatrick, M F; Freestone, S; Lee, M R; Douglas, N J
Abstract : BACKGROUND–Patients with the sleep apnoea/hypopnoea syndrome have increased salt and water excretion at night which has been reported to be associated with an increase in plasma levels of atrial natriuretic peptide (ANP). A study was performed to determine whether any rise in plasma ANP levels was related to nocturnal hypoxaemia. METHODS–Nine patients with sleep apnoea/hypopnoea syndrome were studied on two nights, one breathing air and the other 28% oxygen, the order being randomised. Venous levels of ANP, aldosterone, and renin activity were measured. RESULTS–No decrease in plasma ANP levels on oxygen was seen, and, indeed, there was no evidence of an overnight increase in ANP levels. CONCLUSION–Oxygen therapy does not diminish nocturnal plasma ANP levels in patients with sleep apnoea/hypopnoea syndrome.